Mixed Column Application in Pesticide Residues Analysis - Ribeiro, M. L. [UNESP]; Poleze, L. [UNESP]; Draetta, M. S. [UNESP]; Minelli, E. [UNESP]; Del'Acqua, A. [UNESP] (Soc Brasileira Quimica, 1991)
A clean-up technique for organochlorine pesticide residues analysis was evaluated through the study of the parameters involved in recovery of selected pesticides and in a efficient purification of the extracts. The degree of water deactivation of adsorbvents, the standing time of the silica and the flow rate elution were all significant factors for the development of the procedure. Optimization of the experimental conditions using standard solutions resulted in >88% recoveries for all studied pesticides, except for HCB. The application of the method to lipid samples provided an average residual fat value ca. 0,04%. The data demonstrated the viability of the procedure to promote the pesticide extraction and the purification of the extracts in a single step. The analysis were performed in about 40 min employing small quantities of reagents and solvents.
Keywords: organochlorine; pesticide residues; soybean bagasse; gas chromatography